Thermal conductivity and viscosity of TiO2/MWCNTs (doped 10wt% graphene) - ethylene glycol based nanofluids for different ratio of nanoparticle - Zetty Akhtar, A. M; M. M., Rahman; Kadirgama, Kumaran; S., Rahman; M. A., Maleque (Akademi Baru, 2020)
The use of nanofluids to boost the thermal performance of conventional work fluids has recently shown considerable interest. This paper aims to analyse the thermal conductivity, viscosity and stability of titanium dioxide (TiO2)-multi-walled carbon nanotubes (MWCNTs) nanofluid in the presence of sodium dodecyl benzene sulfonate (SDBS) as a surfactant. The enhancement of thermal physical properties of nanofluids in this study investigated under different concentrations and ratios of the nanoparticle. Ethylene glycol (base fluid), TiO2and CNTs nanoparticle mixed to produce hybrid nanofluid with concentration 0.02 to 0.1 wt.% with 0.02 wt% interval. The mixing ratio of TiO2: MWCNTs was 90:10 and 80:20, meanwhile the ratio of SDBS: MWCNTs was 10:1. The stability of nanofluid was confirmed by using the observation method and zeta potential analysis. The thermal conductivity and viscosity of suspension were measured to determine the relationship between concentration on nanofluid and thermal physical properties. Based on results obtained, zeta potential value for both nanofluid with different ratios range from -50 to -70 mV indicates excellent stability of the suspension. Thermal conductivity of nanofluid increase as nanofluid concentration and temperature increase and also shows enhancement compared to the base fluid. However, the increment in thermal conductivity for nanofluid with ratio 90:10 was more stable and higher throughout the increasing temperature compared to nanofluid with ratio 80:20. Meanwhile, the viscosity value of nanofluid shows decrements over increased temperature and increment over increase volume concentration. In conclusion, the developed nanofluid with both ratios in this study found to be stable, with enhanced thermal conductivity and viscosity.